تفويض المرفق العام في ظل المرسوم التنفيذي 199/ - قمو, عبد الكريم; حمادو, عبد الحق (University of Eloued جامعة الوادي, 2023)
تقنية تفويض المرفق العام لجأت إليها السلطات العمومية بغية النهوض بالقطاع نتيجة للعيوب التي كانت في تسيير المرفق العمل الكلاسيكي. فكان لزاما فتح عقود التفويض ووضع حد لاحتكار القطاع العام. وكما أسلفنا في هذه الدراسة أبرزنا تقنية التفويض وفق المرسوم التنفيذي 18-199 المتعلق بتفويض المرفق العام ، والذي جاء مستدرك بعض النقائص ونزع ما كان مبهم في المرسوم الرئاسي 15-247 المنظم لقانون الصفقات العمومية و تفويضات المرفق العام ، و الذي رسم بذلك التردد الذي كان يكتنف الإدارة ، بهدف التطبيق السليم لعقود التفويض وتحسين أداء الخدمة العمومية في ظل تزايد الحس المدني و تزايد الطلبات إذ تعد تقنية التفويض من انجح الطرق وذلك بإشراك القطاع الخاص ومد له يد العون ليساهم في التنمية المستدامة و النهوض بقطاع المرفق العام. The public utility delegation technique was resorted to by the public authorities in order to advance the sector as a result of the defects that were in the management of the classic public utility. It was necessary to open authorization contracts and put an end to the monopoly of the public sector. As mentioned in this study, we highlighted the authorization technique in accordance with Presidential Decree 15-247 regulating the law of public procurement and public utility authorizations, which drew the hesitation that surrounded the administration and followed it with Executive Decree 18-199 related to the authorization of the public utility, which came to rectify some shortcomings and remove what was vague in the decree The aforementioned aims at the proper application of delegation contracts and improving the performance of public service in light of the increasing civic sense and the increasing demands, as the delegation technique is one of the most successful methods by involving the private sector and extending a helping hand to it to contribute to development .
مذكرة ماستر
Keywords: المرفق العام –التفويض-المرسوم التنفيذي 18/199; Executive Decree 18-199- delegation technique- delegation technique